2013
DOI: 10.2298/jmmb120111041d
|View full text |Cite
|
Sign up to set email alerts
|

SEM/EDX and XRD characterization of silver nanocrystalline thin film prepared from organometallic solution precursor

Abstract: The Ag nano-structured thin films prepared on flat glass substrates have been studied. The ball-like silver nanoparticles have been synthesized in large quantity by using a modified method of hydrolytic decomposition of silver complexes with amino types ligands formed in ethanol aqueous solution. SEM analysis revealed that Ag nanoparticles are all sphere shaped with bimodal size (40 and 70 nm) distribution. The results of XRD powder pattern examination show that Ag nanoparticles are pure phase, well crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 0 publications
5
18
0
Order By: Relevance
“…Treatment of HCT-116 cells at 100 µg/mL revealed that Ag NPs had the maximum cytotoxicity followed by PS extract and Au NPs. PS Similar changes have also been reported on different cancer cell lines after treatment with Ag NPs, which were synthesized using plant extracts [32]. Some previous findings also show the cytotoxic effects of biologically synthesized Ag NPs against cancer cell lines [32,33].…”
Section: Discussionsupporting
confidence: 79%
“…Treatment of HCT-116 cells at 100 µg/mL revealed that Ag NPs had the maximum cytotoxicity followed by PS extract and Au NPs. PS Similar changes have also been reported on different cancer cell lines after treatment with Ag NPs, which were synthesized using plant extracts [32]. Some previous findings also show the cytotoxic effects of biologically synthesized Ag NPs against cancer cell lines [32,33].…”
Section: Discussionsupporting
confidence: 79%
“…According to the image, the largest number of particles in this Figure has an average size of about 20 nm. The result of the SEM image is very similar to the previous results [19]. TEM results Figure 9 shows the image of the transmitted electron microscope of silver NPs by applying all optimized conditions.…”
Section: Characterization Of Silver Nps Synthesized By Extract Of Scrsupporting
confidence: 82%
“…Moreover, while sputtering power increases, the (111) peak intensity becomes stronger as shown in Figure 1(a). This implies an increase in crystallinity and grain size, with (111) plane having the lowest surface energy [13,15,18]. The grain size of the silver film is an important indicator of the crystallization quality, which was calculated using the Scherrer formula.…”
Section: Accepted Manuscriptmentioning
confidence: 99%